Relationship Analysis Between Leaf-Stomata Characteristics with Cocoa Resistance to Vascular-Streak Dieback - Agung Wahyu Soesilo; Poppy Arisandy; Indah Anita Sari; Rudi Harimurti (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Characteristics of leaf-stomata indicate having relationship with  the resistance of  cocoa  to  vascular-streak  dieback  (VSD)  caused  by  Ceratobasidum  theobromae. This  research  has  objective  to  identify  the  relationship  between leaf-stomata   haracteristicsto VSD resistance in order to develop criteria for selection. Trial was establised in  randomized-complete  block design  with three  blocks as replications  in  Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute (ICCRI) using 15  clones  which  had  different  background  on  VSD  resistance.  Leaf-stomata  of  the tested  clones  were characterized  using variables of number of stomata,  stomata size, width  of  opened-stomata  and  size  of  stomata  mouth  in  three  different  level  of  leaf growth,  namely  flush,  young  and  mature.  VSD  resistance  was  assessed  by  scoring the damage in the scale of 0-6 that  the tested clones were classified into five group sof resistance.  Analysis  of  variance  indicated  a  significant  effect  of  cocoa  clone  to  the number of  stomata  in  all categories  of leaf  sample  but the  other leaf-stomata  haracteristics  were  significantly  affected  by  cocoa  clone  just  at  the  young  and  mature leaf.  Correlation  analysis  performed  a  significant inter-correlation  between  variables of leaf-stomata characteristics in young leaf and the score of VSD resistance. However, number of stomata and width of opened-stomata in the mature leaf were significantly correlated  to  the  score  of  VSD  resistance.  Genetic  variance  analysis  showed  a  high category of broad sense heritability for the number of stomata and width of the  penedstomata  in  young  leaf  that  both  of  the  variables  can  be  developed  as  criteria  for selection on  VSD  resistance.